2013
DOI: 10.1021/bi401312r
|View full text |Cite
|
Sign up to set email alerts
|

Base Pair Opening in a Deoxynucleotide Duplex Containing a cis-syn Thymine Cyclobutane Dimer Lesion

Abstract: The cis-syn thymine cyclobutane dimer is a DNA photoproduct implicated in skin cancer. We compared the stability of individual base pairs in thymine dimer-containing duplexes to undamaged parent 10-mer duplexes. UV melting thermodynamic measurements, CD spectroscopy, and 2D NOESY NMR spectroscopy confirm that the thymine dimer lesion is locally and moderately destabilizing within an overall B-form duplex conformation. We measured the rates of exchange of individual imino protons by NMR using magnetization tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In DNA1 and DNA3, the cs CPD is flanked by GC base pairs on either side, whereas it is flanked by one GC (3′ of cs CPD) and one AT (5′ of cs CPD) base pair in DNA2. Work by the Stanley group on melting temperatures of cs CPD-dsDNA with fluorescent bases has shown that the base pairs on the 5′-side of the CPD, including the 5′-T of the cs CPD, are slightly less stable than those on the 3′-side of the CPD. ,, These results are corroborated by a recent NMR study that shows that the 5′-TA base pair of the CPD is more labile than its 3′-TA base pair . Therefore, it seems that the flanking 5′-TA base pair of the cs CPD in DNA2 destabilizes the cs CPD-dsDNA slightly more than a flanking GC base pair.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In DNA1 and DNA3, the cs CPD is flanked by GC base pairs on either side, whereas it is flanked by one GC (3′ of cs CPD) and one AT (5′ of cs CPD) base pair in DNA2. Work by the Stanley group on melting temperatures of cs CPD-dsDNA with fluorescent bases has shown that the base pairs on the 5′-side of the CPD, including the 5′-T of the cs CPD, are slightly less stable than those on the 3′-side of the CPD. ,, These results are corroborated by a recent NMR study that shows that the 5′-TA base pair of the CPD is more labile than its 3′-TA base pair . Therefore, it seems that the flanking 5′-TA base pair of the cs CPD in DNA2 destabilizes the cs CPD-dsDNA slightly more than a flanking GC base pair.…”
Section: Discussionmentioning
confidence: 81%
“…The role of the enzyme in base flipping is not completely clear. A computational study of cs CPD-containing DNA and a recent isothermal calorimetry study of photolyase–substrate binding provided support for binding of photolyase to an extrahelical CPD that spontaneously flips out of the double helix. , However, a recent NMR study of base flipping in cs CPD-containing DNA argued against the spontaneous movement of the cs CPD into an extrahelical position as a viable mechanism …”
mentioning
confidence: 99%
“…A study of CPDs in T-tracts in a rotationally phased nuclesosome core particle found, however, that repair by photolyase is greatly inhibited relative to free DNA and that sites of more efficient repair do not correlate with their rotational position ( 40 ) indicating that steric and other factors may be more important in CPD recognition by photolyase. Another possibility is that a base opposite the CPD is flipping out as observed for T4 endonuclease V binding to a CPD ( 41 ), or as deduced from a recent proton exchange nuclear magnetic resonance study on base pair opening in a CPD-containing DNA duplex ( 42 ). This possibility is less likely, however, since the bases opposite a CPD in position 6 which has the fastest deamination rate, have the lowest temperature factors and would be predicted to have the least flexibility since they are held against the histone core surface.…”
Section: Discussionmentioning
confidence: 99%
“…where: α is known to be approximately equal to unity for the ammonia base catalyst (Wenke, Huiting, Frankel, Lane, & Núñez, 2013), k NH 3 ¼ 4:0 Á 10 8 M −1 S −1 and k NH 3 ¼ 1:1 Á 10 9 M −1 S −1 for T and G, respectively (Moe & Russu, 1992), thus K i X values are readily obtainable from k ex ð½NH 3 Þ dependences.…”
Section: Determination Of Base Pair Opening Temperature (T Bo ) and Mmentioning
confidence: 99%